Patient-reported improvements from use of IMC-2 alone and IMC-2 and Paxlovid® in a Long COVID cohort: a case series - Pridgen, William L.; Putrino, David (Frontiers in Immunology, 2026)
IntroductionLong COVID (LC) is an infection-associated chronic condition and illness (IACCI) with no currently approved treatments. In order to address SARS-CoV-2 persistence and herpesvirus reactivation, which have been implicated as drivers of LC, sustained use of antiviral combinations may be useful in treating patients with the illness.MethodsA convenience sample of patients undergoing an extended course of antiviral therapy was studied. Patients received either 120 days of IMC-2 only (IO) or 120 days of IMC-2 with the addition of 15 days of Paxlovid (IP), prescribed off-label at an outpatient clinic for people with LC. The Patient Global Impression of Change (PGIC) was used to measure therapy response over time, with primary focus on fatigue and secondary focus on brain fog and dysautonomia. Visual analog scales (VAS) were also used to track perceived symptom improvements.ResultsA total of 27 people with LC were approached for treatment, of whom 24 completed one or both protocols. Twelve received the IO protocol, and 12 received the continuous IP combination. Both groups reported reductions in fatigue on the PGIC, but participants receiving IP experienced a statistically significant improvement compared with those receiving IO (p < 0.0001). Similarly, using a VAS, patients in the IP group reported an average 55.3% (p < 0.0001) greater reduction in fatigue than the IO group. Participants who completed the IP intervention demonstrated durable clinical benefit, with symptom improvements remaining consistent at 120-, 305-, and 731-day follow-ups.DiscussionThis small, open-label case series provides pilot evidence supporting the need for a larger trial of combination antivirals for people living with LC. Based on these results, a larger, controlled trial of IMC-2 paired with Paxlovid is recommended.